2005
DOI: 10.1590/s0103-84782005000500017
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of beak and tongue of partrigde Rhynchotus rufescens

Abstract: Twenty adult partridges Rhynchotus rufescens were used to study the morphology of the beak and the tongue. Lengths of the beak and of the tongue were evaluated, and histologic sections of the tongue were stained routinely with hematoxylin-eosin (HE), periodic acid-Schiff (PAS) and Masson’s trichrome stain, later analyzed and described. The beak of the partridge of both sexes are curved, flat, hard and with a sharp extremity, with mean length of 4.90cm for the females and 4,80 for the males. The tongue is chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 5 publications
3
26
0
7
Order By: Relevance
“…As we learned from our study, adipose tissue also surrounds the lingual glands, and thus, movements of the tongue may bring about mechanic stimuli, causing mucus release from the glandular secretory units and ducts. The distribution of such glands and their openings so far studied in birds revealed that the anterior lingual glands have their openings at both sides of the tongue and posterior lingual glands at the surface of the root (Iwasaki and Kobayashi, 1986;Kobayashi et al, 1998;Liman et al, 2001;Jackowiak and Godynicki, 2005;Rossi et al, 2005). Our observations in the domestic goose corroborate the findings of most of the latter authors.…”
Section: Discussionsupporting
confidence: 88%
“…As we learned from our study, adipose tissue also surrounds the lingual glands, and thus, movements of the tongue may bring about mechanic stimuli, causing mucus release from the glandular secretory units and ducts. The distribution of such glands and their openings so far studied in birds revealed that the anterior lingual glands have their openings at both sides of the tongue and posterior lingual glands at the surface of the root (Iwasaki and Kobayashi, 1986;Kobayashi et al, 1998;Liman et al, 2001;Jackowiak and Godynicki, 2005;Rossi et al, 2005). Our observations in the domestic goose corroborate the findings of most of the latter authors.…”
Section: Discussionsupporting
confidence: 88%
“…Lamina propria of the mucosa in the domestic duck is equipped with numerous complex anterior and posterior lingual glands, which are typical for other birds (Iwasaki and Kobayashi 1986; Kobayashi et al 1998; Liman et al 2001; Jackowiak and Godynicki 2005; Rossi et al 2005; Emura et al 2010a, b, 2011). The tongue is characterized by many openings located on the lateral surfaces of the body and the lingual prominence and on the dorsal surface of the root.…”
Section: Discussionmentioning
confidence: 99%
“…In the mammals, it is a muscular tube modified for voluntary and involuntary movement of foodstuffs to and from the stomach [2]. The oesophagus of birds shows histologic differences with that of mammals including glandular lamina propria [1,2], different extension of muscularis mucosae into the mucosal folds [5,9,11], absence of muscularis mucosa in some birds [5,10] and two external smooth muscular layers covered almost completely by the adventitia [1,2]. Consequently, these differences result from different sequential events of the oesophagus histogenesis in these two classes of animals.…”
Section: Introductionmentioning
confidence: 99%